MENINGKATKAN HASIL BELAJAR MATERI HIDROLISIS GARAM PADA SISWA YANG MEMILIKI BERBAGAI GAYA BERPIKIR MELALUI STRATEGI SCIENTIFIC PROBLEM SOLVING DI KELAS XI IPA 2 SMA NEGERI 7 BANJARMASIN - Diah Puji Hastuti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. Action research with two cycles. The main subject of this study was 34 students in XI IPA 2 Senior High School 7 Banjamasin. The instrument of study included learning test, ycreative-critical thinking style test, observation, and polling. The results of this study showed learning result rise from 70.59% on cycle I to 97.06% on cycle II and improved results to higher learning in students with creative thinking style. This rise also followed by teacher activity, students activity, and students responses in teaching process.Keywords: learning result, thinking styles, scientific problem solving.